FEATURES OF USING THE GOOGLE MEET PLATFORM BY STUDENTS OF THE MEDICAL UNIVERSITY IN THE CONDITIONS OF DISTANCE LEARNING - Дикалу, Марьяна; Копчук, Тамара; Драчук, Вера (SWorldJournal, 2021)
The article considers the basic principles and possibilities of using such platforms as Google Meet, Google Forms and MOODLE distance learning server for training medical students at the Department of Bioorganic and Biological Chemistry and Clinical Bioch